AUGUSTUS’S GEOGRAPHY: DURABILITY AND DISCONTINUITY IN THE REGIONALIZATION OF THE ITALIAN TERRITORY - Franco Salvatori (Bollettino della Società Geografica Italiana)
While Augustus gets ready to give a recognizable imperial layout to the political space organized by the city, he wants to give centrality to Italy with an ideal call to the function and values of the Roman republic. The distribution of Italy into regions could meet this purpose, emphasizing, with the unitary, the details of its ethnic-cultural elements, according to a model still verifiable after two thousand years.